Changes for Kaya : a story of courage - Shaw, Janet Beeler, 1937- (American girls collection., 2002)
While looking for Steps High, the horse that had been stolen from her, Kaya faces danger from a sudden mountain fire. Includes historical notes on the Nez Perce Indians.